(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article presents a comprehensive comparative linguistic analysis of the prepositional systems in the Uzbek and English languages, highlighting both structural and functional aspects. Prepositions, as essential grammatical elements, play a crucial role in conveying spatial, temporal, causal, and logical relationships between different components of a sentence. While English, being a predominantly analytic language, relies heavily on prepositions to express grammatical relations, Uzbek, as an agglutinative and Turkic language, often conveys similar meanings through postpositions and affixes. This typological difference serves as the basis for exploring divergences and partial overlaps in usage, semantic scope, and syntactic behavior. The study begins with a classification of prepositions in both languages, examining their etymological origins, frequency, and function within different linguistic contexts. Particular attention is given to polysemous prepositions such as "in", "on", "at" in English, and their functional counterparts in Uzbek, which may be expressed through suffixes (e.g., -da, -ga) or analytic constructions (e.g., ustida, ichida). The article then investigates the challenges of equivalence in translation and second-language acquisition, emphasizing the importance of contextual understanding and collocational patterns. Furthermore, the paper explores how Uzbek learners of English often face difficulties in mastering the use of prepositions due to the absence of one-to-one correspondences, interference from native structures, and differences in word order. Common errors and misunderstandings are analyzed based on learner corpora and examples from both academic and colloquial speech. The article also highlights how digital tools and contrastive grammar teaching methods can enhance the acquisition of accurate prepositional usage. By synthesizing perspectives from typological linguistics, contrastive analysis, and pedagogical grammar, this study provides valuable insights for linguists, language teachers, translators, and students. It ultimately underscores the significance of a nuanced, comparative approach to understanding functional categories like prepositions, which differ greatly across languages but serve universal communicative functions.